2018
DOI: 10.3390/en11040847
|View full text |Cite
|
Sign up to set email alerts
|

Grey Wolf Optimization-Based Optimum Energy-Management and Battery-Sizing Method for Grid-Connected Microgrids

Abstract: In the revolution of green energy development, microgrids with renewable energy sources such as solar, wind and fuel cells are becoming a popular and effective way of controlling and managing these sources. On the other hand, owing to the intermittency and wide range of dynamic responses of renewable energy sources, battery energy-storage systems have become an integral feature of microgrids. Intelligent energy management and battery sizing are essential requirements in the microgrids to ensure the optimal use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Grey wolf optimizer, a newly swarm intelligence algorithm introduced by Mirjalili et al [51], is a powerful meta-heuristic algorithm, which has the ability to compete with other algorithms including PSO, GA, DE and many other algorithms in terms of solution accuracy, minimum computational effort, and aversion of premature convergence [69,70]. Because of these advantages, it has been gained a very big research interest by tremendous audiences from several domains and successfully applied in the fields of global optimization [71], control engineering [72,73], feature selection [74], scheduling problems [75,76] in recent years.…”
Section: Grey Wolf Optimizermentioning
confidence: 99%
“…Grey wolf optimizer, a newly swarm intelligence algorithm introduced by Mirjalili et al [51], is a powerful meta-heuristic algorithm, which has the ability to compete with other algorithms including PSO, GA, DE and many other algorithms in terms of solution accuracy, minimum computational effort, and aversion of premature convergence [69,70]. Because of these advantages, it has been gained a very big research interest by tremendous audiences from several domains and successfully applied in the fields of global optimization [71], control engineering [72,73], feature selection [74], scheduling problems [75,76] in recent years.…”
Section: Grey Wolf Optimizermentioning
confidence: 99%
“…Grey wolf optimizer is one of the metaheuristic algorithms widely applied in energy domain due to the decreased amount of entities. Most of these researches apply the Grey wolf optimizer algorithm directly and solve the issues of smart energy networks . Our proposed modified Grey Wolf Optimizer in MapReduce environment efficiently maintains the balance between exploration and exploitation in the progressing population.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these researches apply the Grey wolf optimizer algorithm directly and solve the issues of smart energy networks. [50][51][52][53] Our proposed modified Grey Wolf Optimizer in MapReduce environment efficiently maintains the balance between exploration and exploitation in the progressing population. In future, we plan to apply our MapReduce-based Modified Grey Wolf Optimizer for solving the problem of creating and ensuring the successful functioning of smart energy networks using a complex of renewable energy sources of various nature.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implemented GWO and compared its results with other algorithms. These studies found that GWO provides competitive optimization results compared to other swarm and evolutionary algorithms such as particle swarm optimization (PSO) [56][57][58], differential evolution (DE) [56], gravitational search algorithm (GSA) [56,57], genetic algorithm (GA) [58] and ant colony optimization (ACO) [59].…”
Section: B Grey Wolf Optimization (Gwo)mentioning
confidence: 99%